Γ-Semihypergroups and Regular Relations. (30th January 2013) - Mirvakili, S.; Anvariyeh, S. M.; Davvaz, B.
Abstract : In this paper we discuss the structure of Γ -semihypergroups. We prove some basic results and present several examples of Γ -semihypergroups. Also, we obtain some properties of regular and strongly regular relations on a Γ -semihypergroup and construct a Γ -semigroup from a Γ -semihypergroup by using the notion of fundamental relation.